JianPi JieDu Recipe Inhibits Epithelial-to-Mesenchymal Transition in Colorectal Cancer through TGF-β/Smad Mediated Snail/E-Cadherin Expression. (16th February 2017) - Liu, Xuan; Ji, Qing; Deng, Wanli; Chai, Ni; Feng, Yuanyuan; Zhou, Lihong; Sui, Hua; Li, Chunpu; Sun, Xiaoting; Li, Qi
Abstract : JPJD was an ideal alternative traditional Chinese medicine compound in the prevention and treatment of CRC, but its underlying mechanisms has not been fully elucidated. In this study, we demonstrated in vitro that TGF- β -induced EMT promoted the invasion and metastasis of CRC cells, reduced the expression of E-cadherin, and elevated the expression of Vimentin. However, JPJD could inhibit the invasive and migratory ability of TGF- β -stimulated CRC cells in a concentration-dependent manner through increasing the expression of E-cadherin and repressing the expression of Vimentin, as well as the inhibition of TGF- β /Smad signaling pathway. Meanwhile, JPJD reduced the transcriptional activities of EMT-associated factors Snail and E-cadherin during the initiation of TGF- β -induced EMT. In vivo, the results demonstrated that JPJD can significantly inhibit the liver and lung metastasis of orthotopic CRC tumor in nude mice, as well as significantly prolonging the survival time of tumor-bearing in a dose-dependent manner. Additionally, JPJD can upregulate the expression of E-cadherin and Smad2/3 in the cytoplasm and downregulate the expression of Vimentin, p-Smad2/3, and Snail in the orthotopic CRC tumor tissues. In conclusions, our new findings provided evidence that JPJD could inhibit TGF- β -induced EMT in CRC through TGF- β /Smad mediated Snail/E-cadherin expression.